2022
DOI: 10.1002/nop2.1344
|View full text |Cite
|
Sign up to set email alerts
|

Moral awareness and its relationship with moral sensitivity among Iranian nursing students: A basis for nursing ethics education

Abstract: The healthcare environment is always fraught with moral issues and challenges for all members of the healthcare team, including nurses as the largest group of service providers in the healthcare system (Rasoal et al., 2017). Due to their continuous attendance to the patients at their bedside, nurses have a major effect on the quality of and patients' satisfaction with healthcare services (Rohde & Domm, 2018;Zamanzadeh et al., 2017). Adherence to ethical principles contributes to the provision of high-quality n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
1
6
0
1
Order By: Relevance
“…Rahmani et al (21) reported good moral awareness among nursing students. Khamis Mohamed et al (22) found that a professional ethics dimension had the highest mean score rated by nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…Rahmani et al (21) reported good moral awareness among nursing students. Khamis Mohamed et al (22) found that a professional ethics dimension had the highest mean score rated by nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…Para peserta tidak diarahkan pada pengembangan nilai karakter dan etika dalam bergaul di kehidupan sehari-hari (Aloni, 2020;Chen, 2020;de Souza, 2019;Edmundson, 2018;Poje, 2023;Rahmani, 2023;Samuelsson, 2020;Singh, 2023;Standish, 2021;Yoder, 2019;Zvereva, 2023). Peserta didik sekarang ini juga terpengaruh dari budaya-budaya asing yang masuk dalam negeri.…”
Section: Pendahuluanunclassified
“…Nurses work in complex area and morally challenging environment where multiple factors like varied diseases, patient demographics, organizational structures and resource limitations can challenge nurses' ethical and professional judgement (Alnajjar & Ebtsam, 2021 ; Haahr et al., 2020 ). Among these settings, the intensive care unit is a specialized workplace where the interactions between care providers (physicians and nurses) and patients and their families can significantly affect nurses' ability to provide high‐quality care (Haahr et al., 2020 ; Rahmani et al., 2023 ). In order to excel in such a dynamic context, nurses must be both professionally and ethically competent.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of existing articles revealed several studies focusing on the ethical awareness of Iranian nurses working in clinical settings. However, these studies primarily examined nurses' knowledge and awareness of ethical codes and principles using questionnaires (Faraji et al., 2018 ; Hoseinialiabadi et al., 2022 ; Rahmani et al., 2023 ). The measurement of nurses' awareness levels and their understanding of the ethical implications of their actions has been neglected.…”
Section: Introductionmentioning
confidence: 99%